Lunar phase and catch success of the striped marlin (Tetrapturus audax) in sport fishing at Los Cabos, Baja California Sur, Mexico - Ponce-Díaz, G; Ortega-García, S; Hernández-Vázquez, S (Revista de Biología Tropical, 2003)
The influence of the lunar phases on the catch-per-unit effort (CPUE) of the striped marlin (Tetrapturus audax) captured by the Cabo San Lucas, Baja California Sur, Mexico sport-fishing fleet from October 1987 to June 1989 was analyzed. The information is from 3 377 fishing trips by 13 vessels that represent about 10 % of the fleet. The analysis of the CPUE showed a maximum in January 1988 and a minimum in February 1989. Taking into account the knowledge of the factors that had influence on the fishing success is important in the resource management. No significant difference during the full moon compared with results during other lunar phases was found.